From Matched Certificates to Related Persons - Rick Mourits; Ingrid K. van Dijk; Kees Mandemakers (Historical Life Course Studies)
For the Netherlands, a rich new data source has become available which contains indexed civil certificates for multiple generations of individuals: LINKS. The current version of the dataset contains information on 1.7 million demographic events for the province of Zeeland in the 19th and early 20th centuries and will be extended to other provinces in the Netherlands in the near future. To be able to study demographic behaviour, life courses and family relations need to be reconstructed from the civil certificates. This paper describes the steps that are taken to move from the LINKS database, which contains digitised birth, marriage, and death certificates and relational information between individuals on these certificates, to LINKS-gen, which contains over six hundred thousand life courses, family reconstructions for up to seven generations, and fertility, marital, mortality, and occupational status information, ready for analysis. We present procedures for variable construction and data cleaning. Furthermore, we give a short overview of the LINKS database, discuss quality checks, and give advice on selection of relevant cases necessary to move from LINKS to LINKS-gen. The paper is accompanied by R-scripts to convert and construct the datafiles.